1996
DOI: 10.1515/bchm3.1996.377.7-8.489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Helix Formation oncis/transIsomerism of Xaa-Pro Bonds Flanking the Helical Segment

Abstract: The trifluoroethanol (TFE)-induced formation of ahelical structures in the peptide hormone calcitonin (salmon) was studied using limited proteolysis combined with capillary zone electrophoresis. A low TFE content in TFE/buffer mixtures was insufficient to introduce secondary structure, but two Lys-Leu bonds were found to have become inaccessible to proteolysis with clostripain. The influence of increasing helical degree of the Thr 6 -Lys 18 (or ThrMyr 22 in the trans conformation) segment on the cis/trans isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The effect is most striking by going from 10 to 20% TFE in buffer ground electrolyte. This is in good agreement with earlier findings from CD measurements in the case of sCT, where an increase in helicity from 5 to 50% has been observed by changing the TFE content from 10 to 20% [16]. The results of our study make it possible to investigate whether or not the separated conformers exhibit differences in their binding interaction to the corresponding calcitonin receptor, of which cloning was previously reported [22, 231. …”
Section: F Thunecke and G Fischersupporting
confidence: 92%
See 2 more Smart Citations
“…The effect is most striking by going from 10 to 20% TFE in buffer ground electrolyte. This is in good agreement with earlier findings from CD measurements in the case of sCT, where an increase in helicity from 5 to 50% has been observed by changing the TFE content from 10 to 20% [16]. The results of our study make it possible to investigate whether or not the separated conformers exhibit differences in their binding interaction to the corresponding calcitonin receptor, of which cloning was previously reported [22, 231. …”
Section: F Thunecke and G Fischersupporting
confidence: 92%
“…The effect, however, is much smaller in aqueous mixtures containing low amounts of organic solvents. For sCT, Meyer et al [16] have reported a threefold increase in 18% TFE compared to pure water. For the dipeptide Phe-Pro, a twofold increase in water containing 25% methanol was measured [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a consequence of the genomic integration site and/or the high copy-number of the plasmid pSK257 nfap paf_signal in the Penicillium genome. High gene dosage was shown to possibly hamper the transcription or translation machinery of microbial cell factories [36, 37]. However, protein-specific determinants, such as the signal sequence, may also modulate heterologous protein production, processing and secretion in the Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, trypsin cleaves after arginine and lysine, while endoproteinase Arg-C cleaves after arginine only (32). Under rare circumstances, however, Arg-C has been shown to cleave after lysine also (46,47). With synthetic substrates, Arg-C exhibits a specificity for arginine that is 100-1000 times greater than that for lysine (48).…”
Section: Discussionmentioning
confidence: 99%